Summary and Implications for the CAADP Agenda [in 2013 Annual Trends and Outlook Report] - Badiane, Ousmane; Makombe, Tsitsi; Bahiigwa, Godfrey (International Food Policy Research Institute, 2014)
The entire agenda of the New Partnership for Africa’s Development (NEPAD) reflects the determination of African countries to put an end to decades of economic decline and deteriorating living conditions, through improved economic and policy governance that leads to better economic growth and poverty reduction outcomes. CAADP, in particular, demonstrates the strategic choice of African leaders to focus on agriculture as a major contributor to growth, poverty reduction, and food and nutrition security. When discussing resilience in relation to CAADP, a key indicator of progress is greater availability and accessibility of food among the poor and most vulnerable. Stronger trade performance by African countries in agricultural markets, in and outside Africa, constitutes an important pathway to that goal. Higher competitiveness and increased market shares generate higher incomes, while better market integration reduces the level of volatility in food markets. Combined, both raise the capacity to absorb supply shocks and price shocks, and thus enhance the resilience of domestic food markets.